The properties of special concrete using bottom ash - Muda, Zulkifle (2004)
This report presents an experimental study to determine the behavior of Special Concrete containing Bottom Ash that was obtained from TNB Janamanjung Coal Power Plant Sdn. Bhd. in Manjung, Perak. This study involved two phases of experiments: 1) Chemical and physical analysis of bottom ash samples 2) The determination of properties of hardened concrete. The properties of hardened lightweight concrete were determined inclusive of compressive strength, ultrasonic pulse velocity and chemical composition, microscopic aspects and durability of hardened concrete. In this study, bottom ash was used as partial replacement of cement and sand in special concrete with the bottom ash being used as 10, 20, 30 and 40 percent of normal Ordinary Portland Cement (OPC). Zero percent bottom ash was used as control sample. For each mix, a total of 15 cubes (100mm x 100mm x 100mm) specimens were prepared. All concrete specimens were subjected to Ultrasonic Pulse Velocity Tests prior to crushing test. Its compressive strength was tested at curing the ages of 3, 7, 14, 28 and 56 days and subsequently further analysis using Scanning Electron Microscopes (SEMS) and Energy Dispersive X-Ray (EDX) Analysis were conducted. Durability test was also conducted to monitor the effect of Iron Pyrites in the bottom ash concrete. The test results showed that the replacement of cement and sand in concrete mixtures have caused the reduction in the workability of fresh concrete and also the compressive strength of concrete. The maximum compressive strength of concrete occurred at 10 percent replacement with bottom ash. In cement replacement, the results from curing in the accelerated curing tank proved that bottom ash was an inert material and it did not help the hydration process of concrete. Besides, the addition of bottom ash will lower the strength of concrete due to the reduction in cement content in the concrete. In sand replacement, the reduction of compressive strength was possibly due to reduced density of concrete as a result of high porosity of concrete after addition of bottom ash. Bottom ash exhibits a long term compressive strength higher than normal OPC concrete. The higher long term compressive strength of partially substituting cement and sand with 10 percent bottom ash is clearly demonstrated by the compressive strength of concretes at 56 days.